Intracellular bacteria targeting anti-infection bone repair composite material and preparation method thereof

By developing nano calcium phosphate/salicyraldehyde D-alanine thiourea gallium complex/liposome composites, the problem of difficult targeted elimination of bacteria in cells is solved, and the effect of targeted antibacterial and anti-inflammatory bone-promoting repair is achieved, which significantly improves the therapeutic effect of bone and joint infections.

CN119680014APending Publication Date: 2025-03-25GUANGDONG INST OF MICROBIOLOGY GUANGDONG DETECTION CENT OF MICROBIOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411893932.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively target and eliminate bacteria in cells, especially in bone and joint infections, resulting in treatment failure and recurrence, and the post-infection inflammation process may continue.

Method used

A nano-calcium phosphate/salicyraldehyde D-alanine thiourea gallium complex/liposome composite material was developed, and it was engulfed by macrophages into infected cells through liposome loading, releasing D-alanine modified gallium ions to identify bacterial cell membrane peptidoglycans, combined with itaconic acid modified nano-calcium phosphate to regulate the inflammatory microenvironment, and achieve targeted antibacterial and anti-inflammatory bone-promoting repair.

Benefits of technology

This composite material can target and effectively eliminate bacteria in cells, has good biocompatibility and intracellular antibacterial effects, and can regulate the inflammatory microenvironment, promote bone repair, and solve the problem of complex bone and joint intracellular anti-infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680014A_ABST
    Figure CN119680014A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-infection bone repair composite material capable of targeting intracellular bacteria and a preparation method thereof.The composite material comprises nano calcium phosphate, a salicylaldehyde D-alanine thiourea gallium complex and lipidosome, the composite material is entrapped by the lipidosome and swallowed by macrophages to enter infected cells; released D-alanine modified gallium ions play a targeted antibacterial role by recognizing peptidoglycan of a bacterial cell membrane, nano calcium phosphate is modified by itaconic acid and is good in dispersity, and the nano calcium phosphate and itaconic acid with an anti-inflammatory effect have a synergistic effect to regulate an inflammatory microenvironment and play a role in promoting bone repair; the composite material has good biocompatibility for vein endothelial vascular cells and osteoblasts, and has the potential of promoting vascular regeneration and bone repair and good intracellular antibacterial effect; the composite material has the activity of targeted inhibition of intracellular bacteria and anti-inflammatory bone repair promotion, and solves the problem of intracellular infection resistance of complex bones and joints clinically at present.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of biomedical materials and relates to an anti-infection bone repair composite material targeting intracellular bacteria and a preparation method thereof. Background technology:

[0002] Bone and joint infections are catastrophic infections that are usually caused by Staphylococcus aureus. Intracellular colonization of S. aureus at the site of infection leads to recurrent disease. Intracellular infection of bone and joint cells induces the production of inflammatory cytokines, which ultimately leads to increased osteoclastogenesis or the release of proteolytic enzymes, resulting in osteolysis and cartilage destruction in osteomyelitis and septic arthritis. Meeting this challenge usually requires prolonged and high-volume use of antibiotics to achieve effective bactericidal concentrations in the target bacterial microenvironment within host cells. Unfortunately, treatment failure and relapse are common due to the limited antimicrobial efficacy of antibiotics in the harsh phagolysosomal environment and the potential for bacterial resistance caused by repeated use of antibiotics. This situation severely compromises the host immune function and may lead to serious consequences, including the risk of death. Therefore, eradication of intracellular bacteria requires the development of alternative therapeutic options that precisely target host cells and endocytosis to selectively eliminate bacteria in the challenging intracellular environment.

[0003] Moreover, even after bacterial eradication, the inflammatory process may persist due to dead bacterial products, pathogen-associated molecular patterns (PAMPs), and products released from the site of injury into native host tissues during infection, such as damage-associated molecular patterns; therefore, new therapeutic options to combat post-infection inflammatory regulation are of great importance. Summary of the invention:

[0004] The present invention aims to provide an anti-infection bone repair composite material that can target intracellular bacteria and a preparation method thereof. The composite material is a nano calcium phosphate / salicylaldehyde D-alanine thiourea gallium complex / liposome composite material, which is engulfed by macrophages through liposome encapsulation and enters the infected cells, and the released D-alanine-modified gallium ions exert targeted antibacterial effects by recognizing bacterial cell membrane peptidoglycan. The nano calcium phosphate is modified by itaconic acid polymer, which not only has good dispersibility, but also the nano calcium phosphate and itaconic acid with anti-inflammatory effects synergistically regulate the inflammatory microenvironment to promote bone repair. The composite material has both targeted inhibition of intracellular bacteria and anti-inflammatory and bone repair-promoting activities, and solves the current difficult problem of complex bone and joint intracellular anti-infection in clinical practice.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing an anti-infective bone repair composite material targeting intracellular bacteria is to encapsulate salicylaldehyde D-alanine thiourea gallium complex and nano calcium phosphate in liposomes to form a nano calcium phosphate / salicylaldehyde D-alanine thiourea gallium complex / liposome composite material.

[0007] The specific steps are:

[0008] 1) Mix equal moles of thiourea, D-alanine and anhydrous sodium acetate, heat at 30-45° C. and dissolve in distilled water, stir for 2 hours, filter to remove suspended impurities, adjust the pH to 3.0, and slowly evaporate at 30° C. to form D-alanine acetate thiourea single crystals;

[0009] 2) dissolving the D-alanine acetate thiourea single crystal obtained in step 1) in 85% ethanol solution, adding an anhydrous ethanol solution of salicylaldehyde or its derivative, stirring at 60-80° C. for 24 h, cooling to room temperature, filtering, washing with 85% ethanol solution and distilled water, and vacuum drying to obtain salicylaldehyde D-alanine thiourea;

[0010] 3) adding the salicylaldehyde D-alanine thiourea obtained in step 2) into anhydrous ethanol, slowly adding an ethanol solution of a gallium salt dropwise under stirring and reflux, reflux reaction for 3 hours, cooling to room temperature, filtering, washing with water and ethanol, and drying to obtain a salicylaldehyde D-alanine thiourea gallium complex;

[0011] 4) The salicylaldehyde D-alanine thiourea gallium complex in step 3) is dissolved in a 25% DMSO aqueous solution, mixed with nano calcium phosphate, and then hydrated with a liposome film to form a suspension. The suspension is treated with an ultrasonic cell disruptor, precooled at -80°C for 12 hours, and then freeze-dried for 48 hours to obtain a nano calcium phosphate / salicylaldehyde D-alanine thiourea gallium complex / liposome composite material.

[0012] Preferably, in step 1), the concentration of thiourea dissolved in distilled water is 0.6 to 1.8 mol / L.

[0013] Preferably, in step 2), the salicylaldehyde or its derivatives include salicylaldehyde, 3,5-dibromosalicylaldehyde, 3,5-diiodosalicylaldehyde, 3-nitrosalicylicylaldehyde, 5-nitrosalicylicylaldehyde, and 5-sodium sulfonate salicylaldehyde.

[0014] Preferably, the molar ratio of thiourea to salicylaldehyde or its derivatives is 1:1.

[0015] Preferably, in step 3), the gallium salt includes gallium nitrate, gallium sulfate, and gallium chloride.

[0016] Preferably, in step 3), the molar ratio of salicylaldehyde D-alanine thiourea to gallium is 1:1.

[0017] Preferably, in step 4), the liposome film is prepared by mixing phospholipid: cholesterol: Tween-80 in a weight ratio of 5:1:4, then dissolving in chloroform and evaporating in vacuum at 40°C; preferably, the weight percentage of phospholipid: salicylaldehyde D-alanine thiourea gallium complex: nano calcium phosphate is 5:(0.1-0.5):(5-7).

[0018] Preferably, in step 4), the conditions for the ultrasonic cell disruptor treatment are: ultrasonic power of 160 W, probe diameter of 6 mm, ultrasonic time of 1 second, stop time of 1 second, and total treatment time of 15 minutes.

[0019] Preferably, in step 4), the nano-calcium phosphate is nano-calcium phosphate modified with itaconic acid polymer.

[0020] The method for preparing nano calcium phosphate modified by itaconic acid polymer comprises the following steps:

[0021] 1) dissolving itaconic acid in distilled water at 65° C., adding sodium hypophosphite monohydrate, stirring to dissolve, and then adding 2,2′-azobis(2-methylpropionamidine) dihydrochloride, stirring evenly, transferring to a sealed container, heating the solution at 65° C. for 24 hours, and freeze-drying to obtain an itaconic acid polymer;

[0022] 2) preparing a calcium chloride aqueous solution and a diammonium phosphate aqueous solution of corresponding concentration according to a Ca:P molar ratio range of 1: (1.5-2), mixing the diammonium phosphate solution and the itaconic acid polymer aqueous solution, adding them to the calcium chloride aqueous solution, stirring at 50°C-80°C and 300rpm for 2-5 hours, controlling the reaction pH value to 10, standing at room temperature for 3 days after stirring, washing with deionized water, and freeze-drying to obtain nano calcium phosphate modified with itaconic acid polymer.

[0023] Preferably, the mass ratio of itaconic acid to sodium hypophosphite monohydrate and 2,2′-azobis(2-methylpropionamidine) dihydrochloride is 3.12:0.2:0.65.

[0024] Preferably, the concentration of the itaconic acid polymer aqueous solution is 5 to 20 g / L.

[0025] Preferably, the aqueous solution of diammonium hydrogen phosphate solution and the aqueous solution of itaconic acid polymer are mixed in a volume ratio of 2:1.

[0026] The present invention also protects the anti-infection bone repair composite material targeting intracellular bacteria prepared by the above preparation method.

[0027] The beneficial effects of the present invention are as follows:

[0028] 1. The present invention provides an anti-infective bone repair composite material that can target intracellular bacteria. The composite material is encapsulated by liposomes and engulfed by macrophages into infected cells. After entering the cells, D-alanine-modified gallium ions are released to exert targeted antibacterial effects by recognizing bacterial cell membrane peptidoglycan; the released itaconic acid oligomer-modified calcium phosphate nanoparticles have good dispersibility, and the itaconic acid with anti-inflammatory effects synergistically regulates the inflammatory microenvironment and exerts a bone repair-promoting effect.

[0029] 2. The anti-infective bone repair composite material of the present invention that can target intracellular bacteria has good biocompatibility with both venous endothelial cells and osteoblasts, has the potential to promote angiogenesis and bone repair, and has good intracellular antibacterial effects. Description of the drawings:

[0030] Figure 1 This is a graph showing the proliferation-promoting effect of the composite material prepared in Examples 1-3 on venous endothelial vascular cells and osteoblasts.

[0031] Figure 2 The graph is a result of the effect of the composite material prepared in Example 1-3 on the levels of the pro-inflammatory factor TNF-α and the anti-inflammatory factor IL-10 when co-cultured with RAW264.7 cells for 24 hours and 8 days. Specific implementation method:

[0032] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.

[0033] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0034] Example 1

[0035] Preparation steps of salicylaldehyde D-alanine thiourea gallium complex:

[0036] 1) 12 mmol of thiourea is mixed with the same mole of D-alanine and the same mole of anhydrous sodium acetate, and dissolved in 20 mL of distilled water at 30-45° C., and then filtered to remove suspended impurities after stirring for 2 hours, and the pH is adjusted to 3.0, and slowly evaporated at 30° C. to form D-alanine acetate thiourea single crystals;

[0037] 2) 1.0 g of the D-alanine acetate thiourea single crystal obtained in step 1) was dissolved in 50 ml of 85% ethanol solution, and 20 ml of anhydrous ethanol solution of 29.5 g / L salicylaldehyde was added, stirred at 60° C. for 24 h, cooled to room temperature, filtered, washed with 85% ethanol solution and distilled water, and dried in vacuo to obtain salicylaldehyde D-alanine thiourea;

[0038] 3) 1.5 g of the obtained salicylaldehyde D-alanine thiourea was added to 20 ml of anhydrous ethanol, and 20 ml of 100.8 g / L gallium nitrate nonahydrate ethanol solution was slowly added dropwise under stirring and reflux, and the mixture was refluxed for 3 h. The mixture was cooled to room temperature, filtered, washed with water and ethanol, and dried to obtain salicylaldehyde D-alanine thiourea gallium complex.

[0039] The salicylaldehyde D-alanine thiourea gallium complex prepared above was dissolved in a 25% DMSO aqueous solution, the itaconic acid polymer-modified nano-β-tricalcium phosphate was dispersed therein, and the nano-β-tricalcium phosphate was loaded into liposomes to form a composite material. The specific preparation steps are as follows:

[0040] 1) at 65° C., 3.12 g of itaconic acid was dissolved in 50 ml of distilled water, 0.2 g of sodium hypophosphite monohydrate was added, and after stirring to dissolve, 0.65 g of 2,2′-azobis(2-methylpropionamidine) dihydrochloride was added, and after stirring evenly, the solution was transferred to a sealed container and heated at 65° C. for 24 hours, and freeze-dried to obtain an itaconic acid polymer;

[0041] 2) preparing 20 ml of 1.0 mol / L calcium chloride aqueous solution and 20 ml of 1.5 mol / L diammonium hydrogen phosphate aqueous solution respectively; mixing the diammonium hydrogen phosphate aqueous solution and 10 ml of 10 g / L itaconic acid polymer aqueous solution, adding the mixture to the calcium chloride aqueous solution, stirring at 50° C. and 300 rpm for 5 hours, controlling the reaction pH value to 10, and allowing to stand at room temperature for 3 days after reacting for 5 hours, washing with deionized water, and freeze-drying to obtain itaconic acid polymer-modified nano-β-tricalcium phosphate;

[0042] 3) A mixture of 5 g of phospholipid, 1 g of cholesterol and 4 g of Tween-80 was dissolved in chloroform, and then vacuum evaporated at 40° C. to form a liposome film, 0.1 g of salicylaldehyde D-alanine thiourea gallium complex was dissolved in 10 ml of 25% DMSO aqueous solution to obtain a stock solution, 5 g of itaconic acid polymer-modified nano β-tricalcium phosphate and salicylaldehyde D-alanine thiourea gallium complex stock solution were mixed, and then hydrated with the liposome film to obtain a suspension, and the suspension was treated with an ultrasonic cell disruptor under the following conditions: ultrasonic power of 160 W, probe diameter of 6 mm, ultrasonic time of 1 second, stop time of 1 second, and total treatment time of 15 minutes; thereafter, the liposome suspension was precooled at -80° C. for 12 hours, and then freeze-dried for 48 hours to obtain itaconic acid polymer-modified nano β-tricalcium phosphate / salicylaldehyde D-alanine thiourea gallium complex / liposome composite material.

[0043] Example 2

[0044] 1) 20 mmol of thiourea is mixed with the same mole of D-alanine and the same mole of anhydrous sodium acetate, and dissolved in 20 mL of distilled water at 30-45° C., and then filtered to remove suspended impurities after stirring for 2 hours, and the pH is adjusted to 3.0, and slowly evaporated at 30° C. to form D-alanine acetate thiourea single crystals;

[0045] 2) 1.0 g of the D-alanine acetate thiourea single crystal obtained in step 1) was dissolved in 85% ethanol solution, 20 mL of 40.3 g / L 5-nitrosalicylic aldehyde anhydrous ethanol solution was added, stirred at 70° C. for 24 h, cooled to room temperature, filtered, washed with 85% ethanol solution and distilled water, and vacuum dried to obtain salicylaldehyde D-alanine thiourea;

[0046] 3) 1.7 g of the obtained salicylaldehyde D-alanine thiourea was added to 20 mL of anhydrous ethanol, and 20 mL of an ethanol solution of 53.8 g / L anhydrous gallium sulfate was slowly added dropwise under stirring and reflux, and the mixture was refluxed for 3 h. The mixture was cooled to room temperature, filtered, washed with water and ethanol, and dried to obtain a salicylaldehyde D-alanine thiourea gallium complex.

[0047] The obtained salicylaldehyde D-alanine thiourea gallium complex is dissolved in a 25% DMSO aqueous solution, the itaconic acid polymer-modified nano-hydroxyapatite is dispersed therein, and the nano-hydroxyapatite is loaded into liposomes to form a composite material. The specific steps are as follows:

[0048] 1) At 65° C., 3.12 g of itaconic acid was dissolved in 50 ml of distilled water, 0.2 g of sodium hypophosphite monohydrate was added, and after stirring to dissolve, 0.65 g of 2,2′-azobis(2-methylpropionamidine) dihydrochloride was added, and after stirring evenly, the solution was transferred to a sealed container and heated at 65° C. for 24 hours, and freeze-dried to obtain an itaconic acid polymer;

[0049] 2) preparing 20 ml of 1.0 mol / L calcium chloride aqueous solution and 20 ml of 1.67 mol / L diammonium hydrogen phosphate aqueous solution respectively; mixing the diammonium hydrogen phosphate aqueous solution and 10 ml of 5 g / L itaconic acid polymer aqueous solution, adding them to the calcium chloride aqueous solution, stirring at 40° C. and 300 rpm for 4 hours, controlling the reaction pH value to 10, and reacting for 5 hours, standing at room temperature for 3 days, washing with deionized water, and freeze-drying to obtain itaconic acid polymer-modified nano-hydroxyapatite;

[0050] 3) A mixture of 2.5 g of phospholipid, 0.5 g of cholesterol and 2 g of Tween-80 was dissolved in chloroform, and then vacuum evaporated at 40° C. to form a liposome film, 0.05 g of salicylaldehyde D-alanine thiourea gallium complex was dissolved in 50 ml of 25% DMSO aqueous solution to obtain a stock solution, 3 g of itaconic acid polymer-modified nano-hydroxyapatite and salicylaldehyde D-alanine thiourea gallium complex stock solution were mixed, and then hydrated with the liposome film to obtain a suspension, and the suspension was treated with an ultrasonic cell disruptor under the following conditions: ultrasonic power of 160 W, probe diameter of 6 mm, ultrasonic time of 1 second, stop time of 1 second, and total treatment time of 15 minutes; thereafter, the liposome suspension was precooled at -80° C. for 12 hours, and then freeze-dried for 48 hours to obtain itaconic acid polymer-modified nano-hydroxyapatite / salicylaldehyde D-alanine thiourea gallium complex / liposome composite material.

[0051] Embodiment 3:

[0052] 1) 36 mmol of thiourea was mixed with D-alanine of the same molar concentration and anhydrous sodium acetate of the same molar concentration, and dissolved in 20 mL of distilled water at 30-45° C., and then filtered to remove suspended impurities after stirring for 2 hours, and the pH was adjusted to 3.0, and slowly evaporated at 30° C. to form D-alanine acetate thiourea single crystals;

[0053] 2) 1.0 g of the D-alanine acetate thiourea single crystal obtained in step 1 was dissolved in 85% ethanol solution, 20 mL of 67.5 g / L 3,5-dibromosalicylaldehyde anhydrous ethanol solution was added, stirred at 80° C. for 24 h, cooled to room temperature, filtered, washed with 85% ethanol solution and distilled water, and dried in vacuo to obtain salicylaldehyde D-alanine thiourea;

[0054] 3) 2.26 g of the obtained salicylaldehyde D-alanine thiourea was added to 20 mL of anhydrous ethanol, and 20 mL of 42.5 g / L anhydrous gallium chloride ethanol solution was slowly added dropwise under stirring and reflux, and the mixture was refluxed for 3 h. The mixture was cooled to room temperature, filtered, washed with water and ethanol, and dried to obtain a salicylaldehyde D-alanine thiourea gallium complex.

[0055] The obtained salicylaldehyde D-alanine thiourea gallium complex was dissolved in a 25% DMSO aqueous solution, the itaconic acid polymer-modified nano-tetracalcium phosphate was dispersed therein, and the nano-tetracalcium phosphate was loaded into liposomes to form a composite material. The specific preparation steps are as follows:

[0056] 1) At 65° C., 3.12 g of itaconic acid was dissolved in 50 ml of distilled water, 0.2 g of sodium hypophosphite monohydrate was added, and after stirring to dissolve, 0.65 g of 2,2′-azobis(2-methylpropionamidine) dihydrochloride was added, and after stirring evenly, the solution was transferred to a sealed container and heated at 65° C. for 24 hours, and freeze-dried to obtain an itaconic acid polymer;

[0057] 2) preparing 20 ml of 1.0 mol / L calcium chloride aqueous solution and 20 ml of 2.0 mol / L diammonium hydrogen phosphate aqueous solution respectively; mixing the diammonium hydrogen phosphate solution and 10 ml of 10 g / L itaconic acid polymer aqueous solution, adding the mixture to the calcium chloride aqueous solution, stirring at 50° C. and 300 rpm for 2 hours, controlling the reaction pH value to 10, and reacting for 5 hours, standing at room temperature for 3 days, washing with deionized water, and freeze-drying to obtain itaconic acid polymer-modified nano-tetracalcium phosphate;

[0058] 3) A mixture of 7.5 g of phospholipid, 1.5 g of cholesterol and 6 g of Tween-80 was dissolved in chloroform, and then vacuum evaporated at 40° C. to form a liposome film, 0.75 g of salicylaldehyde D-alanine thiourea gallium complex was dissolved in 50 ml of 25% DMSO aqueous solution to obtain a stock solution, 10.5 g of itaconic acid polymer-modified nano-tetracalcium phosphate and salicylaldehyde D-alanine thiourea gallium complex stock solution were mixed, and then hydrated with the liposome film to obtain a suspension, and the suspension was treated with an ultrasonic cell disruptor under the following conditions: ultrasonic power of 160 W, probe diameter of 6 mm, ultrasonic time of 1 second, stop time of 1 second, and total treatment time of 15 minutes; thereafter, the liposome suspension was precooled at -80° C. for 12 hours, and then freeze-dried for 48 hours to obtain itaconic acid polymer-modified nano-tetracalcium phosphate / salicylaldehyde D-alanine thiourea gallium complex / liposome composite material.

[0059] Example 4

[0060] The composite materials prepared in Examples 1-3 were subjected to experiments on biocompatibility, intracellular antibacterial effects, pro-inflammatory and anti-inflammatory factors.

[0061] 1) Biocompatibility analysis

[0062] The composite material (0.5 mg / mL) was immersed in DMEM medium at 37°C for 4 weeks. Three tubes were taken out every week and the extract was collected by centrifugation (8000 g, 15 minutes) and sterilized with a 0.22 μm filter to obtain a sterile extract. HUVEC and MC3T3-E1 cells were cultured at 1×10 4 The cells were inoculated at a density of 100 cells / well in a 96-well plate and supplemented with DMEM medium (containing 1% double antibody + 10% calf serum) to 200 μL. The cells were incubated at 37°C, 5% CO2 for 24 hours for cell attachment. The medium was replaced with an equal volume of sterile extract and an equal volume of PBS was used as a control. After 24 hours of culture (37°C, 5% CO2), the cell proliferation was analyzed using the CCK8 kit (Biyuntian, C0038). Cell proliferation effect (%) = (OD T -OD ck ) / OD ck × 100%, where OD ck is the absorbance of PBS control at 450nm, OD T is the absorbance at 450 nm of the experimental group.

[0063] The composite materials in Examples 1-3 have good biocompatibility for HUVEC and osteoblasts (MC3T3-E1), and the range of promoting proliferation of HUVEC is 94.7%-182.2%, and the range of promoting proliferation of osteoblasts is 95.3%-137.5%, and have the potential to promote angiogenesis and bone repair ( Figure 1 ).

[0064] 2) Analysis of intracellular antibacterial effects

[0065] 5.0×10 4Cell / well concentration (24-well plate), culture RAW264.7 macrophages for 24 hours, infect Staphylococcus aureus for 2 hours at a cell / bacteria (MOI) ratio of 10-20, and gently purge the cells once every 15 minutes with a pipette. The cells were then incubated with 50μg / mL gentamicin for 1 hour to remove extracellular bacteria. 500ul2.5wt% composite material PBS suspension was added to each well of RAW264.7 cells infected with Staphylococcus aureus for co-culture for 2 hours, and 500ulPBS was used as a control. Then lysed with PBS containing 0.1% bovine serum albumin and 0.1% Triton X-100. Finally, the cell lysate was diluted with PBS containing 0.05% Tween-20, and 100ul of the cell lysate was taken and spread on solid LB medium for culture. After 24 hours of culture, the Staphylococcus aureus phagocytosed by macrophages was quantitatively analyzed using Image J software. The antibacterial rate was calculated as follows: antibacterial rate (%) = (M0-Mt) / M0×100%, where M0 is the average colony count of CFU in the PBS sample, and Mt is the CFU of the experimental group.

[0066] Through the analysis of intracellular antibacterial effect, the intracellular antibacterial rates of the composite materials in Example 1, Example 2 and Example 3 were 91.3%, 86.7% and 93.3%, respectively.

[0067] 3) Analysis of pro-inflammatory and anti-inflammatory factors

[0068] The revived RAW264.7 cells were diluted with DMEM medium to 1.0×10 5 The cells were inoculated in a 48-well cell culture plate at a concentration of 100ul 2.5wt% composite material extract, 100ul cell solution and 300ul DMEM medium for co-culture for 24 hours and 8 days. The mixed culture medium (100ul 2.5% composite material extract and 400ul DMEM medium) was replaced every 48h, and 100ul PBS was used to replace the extract as a control. The supernatant was collected and the levels of pro-inflammatory factor TNF-α and anti-inflammatory factor IL-10 were tested by TNF-α ELISA kit and IL-10 ELISA kit, respectively ( Figure 2 ).

[0069] The results showed that after 24 hours of co-culture, compared with the control, the M1 expression factor TNF in the three examples was upregulated, and Example 2 showed a significant increase in TNF expression (p<0.05). The M2-related expression factor IL-10 was downregulated. After 8 days of co-culture, the IL-10 factor was significantly upregulated in the three examples (p<0.05).

Claims

1. A method for preparing an anti-infective bone repair composite material targeting intracellular bacteria, characterized in that: The invention is to encapsulate salicylaldehyde D-alanine thiourea gallium complex and nano calcium phosphate in liposomes to form a nano calcium phosphate / salicylicaldehyde D-alanine thiourea gallium complex / liposome composite material.

2. The preparation method according to claim 1, characterized in that: The specific steps are: 1) Mix equal moles of thiourea, D-alanine and anhydrous sodium acetate, heat at 30-45° C. and dissolve in distilled water, stir for 2 hours, filter to remove suspended impurities, adjust the pH to 3.0, and slowly evaporate at 30° C. to form D-alanine acetate thiourea single crystals; 2) dissolving the D-alanine acetate thiourea single crystal obtained in step 1) in 85% ethanol solution, adding an anhydrous ethanol solution of salicylaldehyde or its derivative, stirring at 60-80° C. for 24 h, cooling to room temperature, filtering, washing with 85% ethanol solution and distilled water, and vacuum drying to obtain salicylaldehyde D-alanine thiourea; 3) adding the salicylaldehyde D-alanine thiourea obtained in step 2) into anhydrous ethanol, slowly adding an ethanol solution of a gallium salt dropwise under stirring and reflux, reflux reaction for 3 hours, cooling to room temperature, filtering, washing with water and ethanol, and drying to obtain a salicylaldehyde D-alanine thiourea gallium complex; 4) The salicylaldehyde D-alanine thiourea gallium complex in step 3) is dissolved in a 25% DMSO aqueous solution, mixed with nano calcium phosphate, and then hydrated with a liposome film to form a suspension. The suspension is treated with an ultrasonic cell disruptor, precooled at -80°C for 12 hours, and then freeze-dried for 48 hours to obtain a nano calcium phosphate / salicylaldehyde D-alanine thiourea gallium complex / liposome composite material.

3. The preparation method according to claim 2, characterized in that: In step 1), the concentration of thiourea dissolved in distilled water is 0.6-1.8 mol / L.

4. The preparation method according to claim 2, characterized in that: In step 2), the salicylaldehyde or its derivatives include salicylaldehyde, 3,5-dibromosalicylaldehyde, 3,5-diiodosalicylaldehyde, 3-nitrosalicylicylaldehyde, 5-nitrosalicylicylaldehyde, and 5-sodium sulfonate salicylaldehyde.

5. The preparation method according to claim 2, characterized in that: The molar ratio of thiourea to salicylaldehyde or its derivative is 1:

1.

6. The preparation method according to claim 2, characterized in that: In step 3), the gallium salt includes gallium nitrate, gallium sulfate, and gallium chloride, and the molar ratio of salicylaldehyde D-alanine thiourea to gallium is 1:

1.

7. The preparation method according to claim 2, characterized in that: In step 4), the liposome film is prepared by mixing phospholipid: cholesterol: Tween-80 in a weight ratio of 5:1:4, then dissolving in chloroform and evaporating in vacuum at 40°C; the weight percentage of phospholipid: salicylaldehyde D-alanine thiourea gallium complex: nano calcium phosphate is 5:(0.1-0.5):(5-7).

8. The preparation method according to claim 2, characterized in that: In step 4), the nano calcium phosphate is nano calcium phosphate modified by itaconic acid polymer, and the preparation method comprises the following steps: 1) dissolving itaconic acid in distilled water at 65° C., adding sodium hypophosphite monohydrate, stirring to dissolve, and then adding 2,2′-azobis(2-methylpropionamidine) dihydrochloride, stirring evenly, transferring to a sealed container, heating the solution at 65° C. for 24 hours, and freeze-drying to obtain an itaconic acid polymer; 2) preparing a calcium chloride aqueous solution and a diammonium phosphate aqueous solution of corresponding concentration according to a Ca:P molar ratio range of 1: (1.5-2), mixing the diammonium phosphate solution and the itaconic acid polymer aqueous solution, adding them to the calcium chloride aqueous solution, stirring at 50°C-80°C and 300rpm for 2-5 hours, controlling the reaction pH value to 10, standing at room temperature for 3 days after stirring, washing with deionized water, and freeze-drying to obtain nano calcium phosphate modified with itaconic acid polymer.

9. The preparation method according to claim 8, characterized in that: The mass ratio of itaconic acid to sodium hypophosphite monohydrate and 2,2′-azobis(2-methylpropionamidine) dihydrochloride is 3.12:0.2:0.65; the concentration of the itaconic acid polymer aqueous solution is 5-20 g / L.

10. An anti-infective bone repair composite material targeting intracellular bacteria prepared by the preparation method according to any one of claims 1 to 9.